The GALAH survey: velocity fluctuations in the Milky Way using Red Clump giants. Issue 3 (30th October 2018) - Khanna, Shourya; Sharma, Sanjib; Bland-Hawthorn, Joss; Hayden, Michael; Nataf, David M; Ting, Yuan-Sen; Kos, Janez; Martell, Sarah; Zwitter, Tomaž; De Silva, Gayandhi; Asplund, Martin; Buder, Sven; et al.
ABSTRACT: If the Galaxy is axisymmetric and in dynamical equilibrium, we expect negligible fluctuations in the residual line-of-sight velocity field. Recent results using the APOGEE survey find significant fluctuations in velocity for stars in the mid-plane (|$z$ | <0.25 kpc) out to 5 kpc, suggesting that the dynamical influence of non-axisymmetric features, i.e. the Milky Way's bar, spiral arms, and merger events extends out to the Solar neighbourhood. Their measured power spectrum has a characteristic amplitude of 11 km s −1 on a scale of 2.5 kpc. The existence of such large-scale streaming motions has important implications for determining the Sun's motion about the Galactic Centre. Using Red Clump stars from GALAH and APOGEE, we map the line-of-sight velocities around the Sun ( d  < 5 kpc), and |$z$ | <1.25 kpc from the mid-plane. By subtracting a smooth axisymmetric model for the velocity field, we study the residual fluctuations and compare our findings with mock survey generated by galaxia . We find negligible large-scale fluctuations away from the plane. In the mid-plane, we reproduce the earlier APOGEE power spectrum but with 20 per cent smaller amplitude (9.3 km s −1 ) after taking into account a few systematics (e.g. volume completeness). Using a flexible axisymmetric model the power amplitude is further reduced to 6.3 km s −1 . Additionally, our simulations show that, in the plane, distances are underestimated for high-mass Red Clump stars which can lead to spurious power amplitude of about 5.2 km s −1 . Taking this into account, we estimate the amplitude of real fluctuations to be <4.6 km s −1, about a factor of three less than the APOGEE result.